Hāfizh Qur'an Educational Game as a Media for Memorizing the Qur'an at the Daarul Huffadz Indonesia Islamic Boarding School, Citeureup Branch (Review of the Philosophical Values of Qur'anic Verses) - Hailen Ike Yunida; Anggreni Bako; Muhammad Muwatto'; Yalizar Rahayu Sitorus; Saiful Saiful; Sonia Isna Suratin (Universitas Muhammadiyah Enrekang, 2024)
By making it as content, this study sees the Hāfizh Qur'an educational game as a means for students who are undergoing muroja'ah and helps them in memorizing the Qur'an. The students can then improve their memorization of the Quran because they are so excited or entertained. The design and implementation of learning games about the Qur'an and the reasons for the establishment of the Daarul Huffadz Indonesia Islamic Boarding School Citereup branch are the problems that are being researched. The idea and implementation of the Qur'an hafizh educational game at the Daarul Huffadz Indonesia Islamic Boarding School Citeureup branch is the subject of this qualitative research. Field research is this type of research. Data collection methods include documentation, interviews, and observations. The steps of Miles and Huberman data analysis are data collection, data reduction, and data presentation, which are then used in data analysis techniques. The findings of the study show that the educational game of hafizh Al-Qur'an is in the form of a guessing game including the title of the surah and related verses. Entertain, eliminate boredom, improve memory, engaging, and much more. During the implementation of the Hāfizh Qur'an educational game, students use laptops to solve puzzles to compose the names of the surahs in the Qur'an. In the verse continuation game, the ustadzah read one verse first, then continued by the Citeureup branch students in turn. The purpose of the Hāfizh Qur'an educational game is to keep students engaged, facilitate memorization, and encourage the next generation to remember the Qur'an through its content.